Authenticity as a Mediator of the Relationship Between Power Contingent Self-Esteem and Subjective Well-Being - Wang, Yi’nan; Li, Ziyi (Frontiers in Psychology, 2018)
Drawing on Eastern wisdom and Self-Determination Theory (Deci & Ryan, 1985), the current study conceptualized a new form of maladaptive self-esteem, the power contingent self-esteem, which is extremely contingent on one’s sense of power, and posits it is related to low subjective well-being by making people experience less authenticity. In Study 1, we found that general power contingent self-esteem was consistently linked to low subjective well-being. More importantly, the negative relationship between power contingent self-esteem and subjective well-being was mediated by authenticity. Study 2 further confirmed the mediation effect between power contingent self-esteem role and satisfaction through authenticity across four different roles (work, romance, friendship, and parent-child relationships). The finding of the negative relationship between power contingent self-esteem and subjective well-being via authenticity contributes to understanding the complicated association between power, self-esteem, and life satisfaction.